Psychosocial supports utilized by caregivers of patients with dementia in South western Uganda: A qualitative investigation - Abaasa, Catherine; Obua, Celestino; Wakida, Edith K; Rukundo, Godfrey Zari (Research square, 2019)
Background: Patients with dementia experience problems ranging from mild to severe impairments in daily life activities. In Uganda, like in most other low and middle-income countries, families are a cornerstone in providing care to patients with dementia. Serving as a caregiver for a person with Alzheimer’s disease is a physically, emotionally and financially demanding role, that is associated with increased stress, depression, fatigue, and financial strain. These have often resulted in elder abuse or neglect of the patients. Currently, data on psychosocial supports available to caregivers of patients with dementia in Uganda is not available. Methods: We conducted a qualitative assessment of the psychosocial supports available to caregivers of patients with Alzheimer’s disease and related dementias in southwestern Uganda, including the content of the formal and informal support interventions and by whom they are delivered. Results: Medical practitioners provide educational support on the diagnosis and prognosis of dementia, but may not provide emotional support in the form of counseling to caregivers of patients with dementia. Caregivers in Southwestern Uganda, receive unstructured emotional and instrumental support from sources outside of the medical system such as family and community, which leave the Caregivers in confusion. Conclusions: The medical care system offers some information about the clinical presentation of Alzheimer’s disease but little or no psychosocial support to the Caregivers of patients with the disease. This has implications for how families and Caregivers cope with the day-to-day care of patients with Alzheimer’s disease in Uganda and calls for institutionalization of structured psychosocial support for Caregivers to improve the care given to Alzheimer’s patients.
Keywords: Alzheimer’s disease; Dementia; LMIC; Psychosocial support; Caregiver